2018
DOI: 10.1097/mpa.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nucleotide-Binding and Oligomerization Domain-Like Receptors in the Intestinal Injury of Severe Acute Pancreatitis in Rats

Abstract: The NLRs, including NOD1, NOD2, and NLRP3, were involved in the intestinal injury in SAP through a caspase-1 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Studies focusing on TLRs, such as the interaction between TLR4 and lipopolysaccharide (LPS), have established a well-known link between the microbiota and the host (Sharif et al, 2009;Cao et al, 2018). Recently, other cytosolic receptor NLRs have attracted increasing attention for their significant role in inflammation and immunity, especially in SAP (Clarke et al, 2010;Xu et al, 2018). Tsuji et al showed that NOD1 activation in acinar cells by gut microbiota played an indispensable role in the occurrence of cerulein-induced AP (Tsuji et al, 2012), where diaminopimelic acid (DAP) from cell wall peptidoglycans of gram-negative bacteria and particular gram-positive bacteria is a ligand for NOD1 that can induce innate immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on TLRs, such as the interaction between TLR4 and lipopolysaccharide (LPS), have established a well-known link between the microbiota and the host (Sharif et al, 2009;Cao et al, 2018). Recently, other cytosolic receptor NLRs have attracted increasing attention for their significant role in inflammation and immunity, especially in SAP (Clarke et al, 2010;Xu et al, 2018). Tsuji et al showed that NOD1 activation in acinar cells by gut microbiota played an indispensable role in the occurrence of cerulein-induced AP (Tsuji et al, 2012), where diaminopimelic acid (DAP) from cell wall peptidoglycans of gram-negative bacteria and particular gram-positive bacteria is a ligand for NOD1 that can induce innate immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…intestinal bacterial translocation; however, its pathogenesis has yet to be fully studied. [1][2][3][4] Studies have found that the leading causes of death are secondary bacterial infections after pancreatic tissue necrosis in SAP, subsequent systemic inflammatory response syndrome, and multiple organ failure. [2][3][4] Related experimental studies have confirmed that the bacterial infection of SAP is caused by intestinal bacterial translocation attributed to the SAP-induced destruction of the intestinal mucosal barrier.…”
Section: Effects Of Emodin On Intestinal Mucosal Barrier By the Upregulation Of Mir-218a-5p Expression In Rats With Acute Necrotizing Panmentioning
confidence: 99%
“… 1 SAP may be related to the mechanisms of self-digestion of the pancreas, the cascade of inflammatory mediators caused by pancreatic tissue damage, pancreatic blood circulation disorder induced by inflammatory mediators and vasoactive substances, and secondary infection of the pancreas due to intestinal bacterial translocation; however, its pathogenesis has yet to be fully studied. 1 4 Studies have found that the leading causes of death are secondary bacterial infections after pancreatic tissue necrosis in SAP, subsequent systemic inflammatory response syndrome, and multiple organ failure. 2 4 Related experimental studies have confirmed that the bacterial infection of SAP is caused by intestinal bacterial translocation attributed to the SAP-induced destruction of the intestinal mucosal barrier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, longterm total parenteral nutrition (TPN) can precipitate intestinal barrier dysfunction and induce or aggravate systemic inflammatory responses and multiple organ dysfunction. In recent years, early enteral nutrition (EEN) was demonstrated to play a significant role in protecting the integrity of intestinal mucosal structures and functions, alleviating systemic inflammatory response, and preventing shifts in bacterial populations (Xu et al, 2018;Zhang et al, 2018). In addition, EEN can alleviate augmented immune responses in the early stages of SAP, thus avoiding the emergence of immunosuppression (Sun et al, 2013).…”
Section: Introductionmentioning
confidence: 99%